1997
DOI: 10.1111/j.1751-1097.1997.tb03208.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Photodynamic Therapy as Compared to UVC and Ionizing Radiation in Human and Murine Lymphoblast Cell Lines

Abstract: The mutagenicity of photodynamic therapy (PDT) using red light and either Photofrin (porfimer sodium) (PF) or aluminum phthalocyanine (AlPc) as the photosensitizer was determined at the thymidine kinase (TK) locus in the human lymphoblastic cell lines, TK6 and WTK1, and was compared to the mutagenicity of UVC and X-radiation in these cells as well as the mutagenicity of PDT in murine L5178Y lymphoblastic cell lines. Photodynamic therapy was found not to be mutagenic in TK6 cells, which possess an active p53 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…However, the potential of PDT to induce genotoxic damage seems to be relatively low compared with ionising radiation or chemotherapy (Evans et al, 1997). This may, in part, be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the potential of PDT to induce genotoxic damage seems to be relatively low compared with ionising radiation or chemotherapy (Evans et al, 1997). This may, in part, be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Singlet oxygen, the major mediator of the PDTinduced photochemical reaction (Henderson and Dougherty, 1992), has a very short diffusion distance of 0.01 mm and a very short lifetime of 0.01 ms (Moan and Berg, 1991). The photochemical reaction may therefore reach only DNA that is located very close to the nuclear membrane (Evans et al, 1997). Oxidative damage leading to single-strand breaks and alkali-labile sites, DNA-protein crosslinks and DNA degradation, as well as to chromosome aberrations has been reported (Evans et al, 1997; Oleinick and Evans, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PDT results in DNA lesions such as single-strand breaks and DNA degradation as well as in chromosome aberrations (Evans et al 1997;Oleinick and Evans 1998). DNA damage induces several cellular responses including DNA repair and the triggering of apoptotic pathways (Niida and Nakanishi 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AGR2 is also able to mediate export of p53 from the nucleus into the cytoplasm better upon UVC irradiation [25]. UVC is a known pro-oxidizing stimulus in cells [45,46] and these data allow a model to be developed that proposes AGR2 protein activity might be stimulated by stresses present in a pro-oxidizing environment revealing a potentially physiological role for dimer assembly in AGR2-mediated oncogenesis.…”
Section: Discussionmentioning
confidence: 99%